The effectiveness of the application of project based learning with video content toward students' interests and learning outcomes in graphic design printing subject - Muhammad Yusuf Farizi; Dwi Maryono; Febri Liantoni (Journal of Informatics and Vocational Education, 2020)
This study aims to find out the improvement and effectiveness of students' learning interests and learning outcomes in using project-based learning models in graphic design printing subjects. The method in this research uses a quantitative quasi-experimental design method. Data collection is done through questionnaires and pretest-posttest controls. The subjects in this study were class XI Multimedia 2 as experimental class and XI Multimedia 1 as control class. The results showed differences in students' learning interests and learning outcomes after using the project-based learning model. This is evidenced by the first hypothesis test using t-test in posttest result of 0.00 which means less than an error level of 0.05, so the conclusion of both classes has a significant difference. In the second hypothesis test using the N-Gain test on learning interests in the experimental class was greater than the control class (41.21 > 20.77). As well as the learning outcomes of the N-Gain (50.30 > 24.49). Therefore, it is concluded that there is an increase in students' interest and learning outcomes in the experimental class.